An analysis of research methods utilized in five top, practitioner-oriented LIS journals from 1980 to 2019 - Lund, Brady D.; Wang, Ting (Journal of documentation, 2021)
PurposeThis study examines research methods utilized in five practitioner-oriented research journals – College and Research Libraries, Information Technology and Libraries, Journal of the Medical Library Association, Library Resources and Technical Services and Reference and User Services Quarterly. The study fills gaps identified in existing content analyses of methods in practitioner-based LIS research publications.Design/methodology/approachBased on analysis standards and coding schemes supplied by the studies of Kalervo Jarvelin and Pertti Vakkari, as well as Heting Chu, this study identifies the primary research method utilized in 6,387 articles published in these five journals from 1980 to 2019. Trends in the frequencies with which various research methods were used are identified and presented using a series of visualizations.FindingsSignificant shifts have occurred in the research methods used by articles in these practitioner-based journals over the past four decades. Notably, the proportion of case studies has dropped substantially, particularly among College and Research Libraries and Journal of the Medical Library Association articles. Diversity of research methods utilized in articles has increased over time, with College and Research Libraries, in particular, having a significant proportion of articles in recent years that employ data analytic or qualitative approaches.Originality/valueWhile similar approaches have been used to examine research methods among other LIS journals, this study is the first to focus primarily on practitioner-based journals and document continuous change (as opposed to sampling a few years) over an extended, 40-year period.